The Thermostable Enzyme Genes of the dTDP-L-Rhamnose Synthesis Pathway (rmlBCD) from a Thermophilic Archaeon - Teramoto, Maki; Zhang, Zilian; Shizuma, Motohiro; Kawasaki, Takashi; Kawarabayasi, Yutaka; Nakamura, Noriyuki (IntechOpen, 2012)
None